Editorial: Identification of in vivo markers for human polarized macrophages: a need that's finally met. Issue 4 (1st October 2015) - Williams, Kenneth C.; Kim, Woong‐Ki
Abstract : Discussion on the identification of M1 and M2 macrophage markers in humans, and their clinical relevance.